EFFECTIVENESS OF SELF INSTRUCTIONAL MODULE (SIM) ON KNOWLEDGE REGARDING THE ILL EFFECTS OF INTERNET ADDICTION AMONG ADOLESCENTS - Jincy Joy; Mary Rappai; Anumol (Indian Journal of Psychiatric Nursing)
With the increasing importance of internet and online usage by all different sectors of the society which is seen increasing dramatically, pathological use of internet in other words internet addiction is becoming more common in society. There is an urgent need to recognize and respond to the reality of internet addiction and the threat of its rapid expansion. The aim of the study was to assess and evaluate the effectiveness of the Self Instruction Module(SIM) on level of knowledge regarding internet addiction among adolescents a pre test post test pre experimental design was adopted and study was done at Army Public School Secundarabad among 70 students between the age group of 15-18years. The study findings revealed that the overall mean percentage in pre-test is 33% and in post-test is 61% in their knowledge scores as measured by improvement in mean percentage from pre test to post test (p <0.05).